Multiple nuclear gene phylogenetic analysis of the evolution of dioecy and sex chromosomes in the genus Silene. - Gabriel A B Marais; Alan Forrest; Esther Kamau; Jos Käfer; Vincent Daubin; Deborah Charlesworth (PLoS ONE, 2011)
In the plant genus Silene, separate sexes and sex chromosomes are believed to have evolved twice. Silene species that are wholly or largely hermaphroditic are assumed to represent the ancestral state from which dioecy evolved. This assumption is important for choice of outgroup species for inferring the genetic and chromosomal changes involved in the evolution of dioecy, but is mainly based on data from a single locus (ITS). To establish the order of events more clearly, and inform outgroup choice, we therefore carried out (i) multi-nuclear-gene phylogenetic analyses of 14 Silene species (including 7 hermaphrodite or gynodioecious species), representing species from both Silene clades with dioecious members, plus a more distantly related outgroup, and (ii) a BayesTraits character analysis of the evolution of dioecy. We confirm two origins of dioecy within this genus in agreement with recent work on comparing sex chromosomes from both clades with dioecious species. We conclude that sex chromosomes evolved after the origin of Silene and within a clade that includes only S. latifolia and its closest relatives. We estimate that sex chromosomes emerged soon after the split with the ancestor of S. viscosa, the probable closest non-dioecious S. latifolia relative among the species included in our study.